INVESTIGATION OF WOUND HEALING ACTIVITY OF METHANOLIC EXTRACT OF STEM BARK OF MIMUSOPS ELENGI LINN. - Gupta, N.; Jain, U.. K. (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
The present study was aimed to evaluate the wound healing activity of extract of bark part of Mimusops elengi. It is well-known plant in Indian traditional medicines. On the basis of traditional use and literature references, this plant was selected for wound healing potential. A methanolic extract of bark parts of Mimusops elengi was examined for wound healing activity in the form of ointment in three types of wound models on mice: the excision, the incision and dead space wound model. The extract ointments showed considerable response in all the above said wound models as comparable to those of a standard drug Betadine ointment in terms of wound contracting ability, wound closure time, tensile strength and dry granuloma weight. Histological analysis was also consistent with the proposal that Mimusops elengi bark extract exhibits significant wound healing